Digital Marketing Training Initiative for MSME Food Vendors Amidst the COVID-19 Pandemic through Participatory Action Research - Judiono, Judiono; Ernawati, Ernawati; Juniadi, Saiful; Eswatini, George (Bisma : Bimbingan Swadaya Masyarakat, 2024)
This study employs Participatory Action Research (PAR) to empower MSME food vendors in Wadungasri Waru Sidoarjo Village through intensive digital marketing training. By actively involving the community in the design and implementation of the program, the approach ensured that the training was tailored to the vendors' specific needs and challenges during the COVID-19 pandemic. The intervention focused on equipping the vendors with essential digital marketing tools and strategies, with an emphasis on practical, real-world application. The results demonstrated a significant increase in sales for several participants, highlighting the effectiveness of digital marketing in enhancing business sustainability and market reach. This study underscores the importance of participatory methods in fostering community empowerment, promoting long-term business growth, and addressing economic disruptions caused by the pandemic.